How Does Meaning-Centered Coping Influence College Students’ Mental Health? The Mediating Roles of Interdependent Self-Construal and School Connectedness - Qin Lu; Qian Chen; Yuanhao Zhang; Zongkui Zhou (Behavioral Sciences)
Meaning-centered coping is regarded as an effective strategy for managing stress and preventing mental disorders. However, it remains unclear how it influences mental health by affecting both the self and social connection dimensions. This study investigated 856 college students through a questionnaire, examining how meaning-centered coping affects their mental health (depression and anxiety). Additionally, this study explored the roles of interdependent self-construal and school connectedness as mediators in this process. The results indicate that meaning-centered coping influences mental health either via the mediation of school connectedness alone (indirect effect for depression: β = −0.08, 95% CI [−0.11, −0.04]; for anxiety: β = −0.06, 95% CI [−0.10, −0.03]) or via the sequential mediation of interdependent self-construal and school connectedness (indirect effect for depression: β = −0.08, 95% CI [−0.11, −0.05]; for anxiety: β = −0.06, 95% CI [−0.10, −0.04]). This study reveals that college students who are skilled at seeking and reconstructing their sense of meaning can effectively cope with stress and alleviate related depression and anxiety. This coping mechanism operates through perceived school connectedness or through activated interdependent self-construal followed by perceived school connectedness, subsequently reducing anxiety and depression induced by chronic stress. This study theoretically deepens the comprehension of the mechanism on meaning-centered coping, while practically, the findings provide valuable insights for educating training college students to leverage the wisdom of meaning theory to sustain their mental health in future challenges.